IgG4-Related Kidney Disease and IgG4-Related Retroperitoneal Fibrosis - Kawano, Mitsuhiro; Yamada, Kazunori (Seminars in Liver Disease, 2016)
Immunoglobulin G4-related kidney disease (IgG4-RKD) is the collective name encompassing renal parenchymal and renal pelvic lesions. The hallmark of renal parenchymal lesions of IgG4-related disease is plasma cell-rich tubulointerstitial nephritis with numerous IgG4-positive plasma cells and characteristic fibrosis. In addition, glomerular lesions are sometimes present, with membranous glomerulonephritis being the most common. Although IgG4-RKD shows good responsiveness to corticosteroid therapy, follow-up imaging studies have revealed that partial cortical scars persist when the start of therapy is delayed. In this review, the authors provide an overview of the latest knowledge of IgG4-RKD, focusing in particular on its pathological and imaging characteristic features.
Keywords: immunoglobulin G4-related kidney disease; tubulointerstitial nephritis; membranous glomerulonephritis; retroperitoneal fibrosis; hydronephrosis